1981
DOI: 10.1080/10862968109547412
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Metaphor in Children's Recall of Expository Passages

Abstract: Abstract. In a series of three studies, the facilitative effect of metaphors on children's recall of expository passages was evaluated. In Experiment 1, with sixth grade subjects and an unfamiliar passage, metaphor target structures were recalled better than their literal paraphrases. In Experiment II, using third grade subjects and a more familiar passage, there were no differences between metaphor and literal versions of passage in terms of the recall of target structures. In Experiment III, which was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Ortonv, 1975;Petrie, 1979], When the object or event referenced by the vehicle is wellknown and the topic object or event rela tively unknown, a metaphor funtions to pro vide directions for exploring the topic through what is already known of the vehicle. When the topic of a passage was relatively unfamiliar, 8-and 11-year-old children re called target sentences more often when the sentence was a metaphor (with a familiar vehicle) than when it was a literal paraphrase [Pearson et al, 1979], These results lend credence to the idea that metaphors can func tion to bridge new and old information in unfamiliar textual contexts.…”
Section: Facilitating Children's Recall Of Figurative Language In Texsupporting
confidence: 63%
See 1 more Smart Citation
“…Ortonv, 1975;Petrie, 1979], When the object or event referenced by the vehicle is wellknown and the topic object or event rela tively unknown, a metaphor funtions to pro vide directions for exploring the topic through what is already known of the vehicle. When the topic of a passage was relatively unfamiliar, 8-and 11-year-old children re called target sentences more often when the sentence was a metaphor (with a familiar vehicle) than when it was a literal paraphrase [Pearson et al, 1979], These results lend credence to the idea that metaphors can func tion to bridge new and old information in unfamiliar textual contexts.…”
Section: Facilitating Children's Recall Of Figurative Language In Texsupporting
confidence: 63%
“…The story materials were developed based on prior research on comprehension of metaphors in text [Pearson et al, 1979]; thus, we used metaphors in which the vehicle (the word used metaphorically) ref erenced objects familiar to the children, and the topic (what the metaphor was about) referenced objects that were relatively unfamiliar. Ten teachers of 5-ycar-olds rated how familiar certain objects (both animate and inanimate) and events were to 5-ycar-olds.…”
Section: Methodsmentioning
confidence: 99%
“…Students who received the metaphorical version learned more. Similarly, Pearson, Raphael, Te Paske and Hyser (1979) found that children were better able to remember metaphorical descriptions than their literal equivalents. Likewise, Reynolds and Schwartz (1983) found that gist recall of passages containing metaphorical conclusion statements was superior to gist recall of the same passages containing literal concluding statements.…”
Section: Metaphor and The Facilitation Of Learningmentioning
confidence: 95%
“…Studies of the processing of metaphors in context indicate that metaphors are just as quickly comprehended as literal sentences when preceded by a long introduction (Ortony, Schallert, Reynolds, & Anton, 1978) and that they are recognized more often than literal sentences and judged more understandable in than out of text (Yarbrough & Blaubergs, 1980). Some researchers have demonstrated adults' improved comprehension and recall of stories with metaphors (Reynolds & Schwartz, 1983) and elementary school children's improved memory for unfamiliar expository texts with metaphors (Pearson et al, 1981). Other studies of the effect of including metaphors in text have demonstrated no consistent differences in the memory for or comprehension of text (Arter, 1976;Elam, 1978).…”
mentioning
confidence: 94%
“…Studies of memory for metaphor and of metaphoric processing can be divided into the many that present the metaphors as isolated stimuli (e.g., Harris, 1976) and the few that present metaphoric sentences embedded in a prose context (e.g., Bell, 1980;Pearson, Raphael, Te Paske, & Hyser, 1981; We wish to express our appreciation to David Lohman, to Cathy Roller, and to three anonymous reviewers for comments on an earlier version of this article, and to Bonnie Meyer and Bruce Britton for consultation on the scoring procedure.…”
mentioning
confidence: 99%